REGIONAL DIALECT VARIATION IN ENGLISH LANGUAGE OF TABLE TENNIS TERMS IN INDONESIAN TABLE TENNIS ORGANIZATIONS FOR THE SPORT MAJOR - Mauldy, Annisa; Nur'Aini, Siti; Senowarsito, Senowarsito (Universitas PGRI Semarang, 2025)
This study explores the use and variation of table tennis terms in Indonesia through a corpus-based analysis by compiling and examining a specialized corpus consisting of coaching manuals. The research identifies the most frequently used terms, their linguistic patterns, and regional variations influenced by local dialects. The study highlights inconsistencies in term usage, translation from international sources, and the influence of Indonesian linguistic structure on sports terms. Results show that while some terms align closely with international standards set by the International Table Tennis Federation (ITTF), A corpus of Indonesian-language texts related to table tennis, comprising coaching manuals, online articles, and interview transcripts, was compiled and analyzed to identify frequently used terms, regional variations, and term consistency. Quantitative analysis was used to determine frequency and collocation patterns. At the same time, qualitative data from interviews with coaches, athletes, and referees explored how dialectical influences and contextual usage affect term adoption and understanding. The findings reveal inconsistencies in terms usage across regions, influenced by local dialects and a lack of standardized translation from English.